Digital Governance Strategy Through E-Buddy for Administrative Optimization: Strategi Tata Kelola Digital Melalui E-Buddy untuk Optimalisasi Administrasi - Maryono; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The acceleration of digital transformation in governance has become a global necessity to improve transparency, accountability, and efficiency in public administration. Specific Background: In Indonesia, particularly in Sidoarjo Regency, bureaucratic reform following the Covid-19 pandemic has encouraged the adoption of e-government initiatives through digital applications such as e-Buddy. Knowledge Gap: However, limited studies have explored systematic strategies for developing and sustaining e-government applications at the regional level, particularly concerning interoperability, human resources, and administrative integration. Aims: This study aims to analyze the development strategy of e-Buddy as an e-government platform supporting administrative governance in Sidoarjo Regency. Results: Findings reveal that e-Buddy was developed through three strategic stages—preparation, consolidation, and stabilization—resulting in improved efficiency, accountability, and coordination in digital correspondence. Novelty: The research provides a structured framework for local e-government development by integrating administrative, technical, and human resource dimensions. Implications: The study offers policy insights for regional governments to strengthen digital governance and align local systems with national e-government standards. Highlights: Three-phase e-government development framework identified. Strengthened administrative efficiency and inter-agency collaboration. Provides a model for sustainable local digital governance. Keywords: E-Government, E-Buddy, Public Administration, Digital Transformation, Good Governance